The first zoeal stage of the deep-sea crab Tetraxanthus rathbunae (Brachyura: Pseudorhombilidae): a morphological description - Bochini, Gabriel L.; Santos, Rafael C.; Zara, Fernando J.; Costa, Rogério C.; Mantelatto, Fernando L. (Zootaxa, 2022)
The description of the first zoea stage of Tetraxanthus rathbunae Chace, 1939, the third known zoea of Pseudorhombilidae and the first for Tetraxanthus, was carried out from laboratory hatched larvae. Their morphology differs from other pseudorhombilid species previously described primarily in the number and type of setae on the antennule, antennal exopod, maxilla, first maxilliped, and second maxilliped. These zoeae, however, share the same number of spines on the carapace (rostral, dorsal, and lateral), absence of the endopod on the antenna, long and well-developed spinose protopod, maxillary exopod with four marginal plumose setae and a robust posterior process, the absence of setae on the basis of the second maxilliped, and the presence of three lateral spines on each side of the furca. The results obtained in the present study are of great importance in being only the third known first stage pseudorhombilid zoea and the first for the Tetraxanthus, as well as in contributing to the identification of brachyuran planktonic zoea. Additionally, it also provides information that can help elucidate pseudorhombilid phylogeny.